1997
DOI: 10.1007/s004420050278
|View full text |Cite
|
Sign up to set email alerts
|

Does nitrogen nutrition restrict the CO 2 response of fertile grassland lacking legumes?

Abstract: The extent of the response of plant growth to atmospheric CO enrichment depends on the availability of resources other than CO. An important growth-limiting resource under field conditions is nitrogen (N). N may, therefore, influence the CO response of plants. The effect of elevated CO (60 Pa) partial pressure (pCO) on the N nutrition of field-grown Lolium perenne swards, cultivated alone or in association with Trifolium repens, was investigated using free air carbon dioxide enrichment (FACE) technology over 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
109
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(126 citation statements)
references
References 25 publications
12
109
3
Order By: Relevance
“…However, there was a clear and consistent dominance hierarchy among species along the N gradient, which was maintained under elevated CO # . Predominance of the effect of N over that of CO # has already been documented for two-species mixtures of grasses and legumes Schenk et al, 1997 ;Zanetti et al, 1997) and more complex communities (Zangerl & Bazzaz, 1984 ; Response to CO 2 of the biomass of species grown as isolated plants # of species are calculated as the ratio of smoothed plant dry weight under elevated CO # to that under ambient CO # ; they are plotted for all concentrations of N. Danthonia richardsonii ; filled circles ; Lotus pedunculatus ; filled triangles, apex up ; Phalaris aquatica ; filled squares ; Trifolium repens, filled triangles, base up. y l x, dotted line.…”
Section: mentioning
confidence: 91%
“…However, there was a clear and consistent dominance hierarchy among species along the N gradient, which was maintained under elevated CO # . Predominance of the effect of N over that of CO # has already been documented for two-species mixtures of grasses and legumes Schenk et al, 1997 ;Zanetti et al, 1997) and more complex communities (Zangerl & Bazzaz, 1984 ; Response to CO 2 of the biomass of species grown as isolated plants # of species are calculated as the ratio of smoothed plant dry weight under elevated CO # to that under ambient CO # ; they are plotted for all concentrations of N. Danthonia richardsonii ; filled circles ; Lotus pedunculatus ; filled triangles, apex up ; Phalaris aquatica ; filled squares ; Trifolium repens, filled triangles, base up. y l x, dotted line.…”
Section: mentioning
confidence: 91%
“…Mixed with atmospheric CO 2 this resulted in a δ 13 C value of the CO 2 above the plot of −18‰, significantly lower than that of atmospheric CO 2 (−8‰). For experimental details see Zanetti et al (1997). The sampled plots received N-fertilization of ca.…”
Section: Site Descriptionsmentioning
confidence: 99%
“…Indeed, higher N 2 O emissions were measured in high Nfertilized L. perenne monoculture under elevated pCO 2 [1,28]. Anyway, long-term CO 2 enrichment experiments have shown that N may become a limiting factor for the reaction of plants (including grasses) to elevated pCO 2 [14,58]. In the studied (N-limited) plots, experimental results suggested that pCO 2 treatment had no significant effect on apparent N uptake and transformations [22,48].…”
Section: Nitrate-dissimilating Pseudomonas Frequency Under Elevated Pmentioning
confidence: 99%